Pattern of edible oil consumption and practice of reuse: A health concern - Ajeet Saoji; Prachi Saoji; Shilpa Hajare; Pranita Dharmadhikari (Journal of Family Medicine and Primary Care)
Background: The per capita consumption of edible oil in Indian households has risen substantially in the last decade contributing to the rising incidence of non-communicable diseases (NCDs). Increasing prevalence of reuse of edible oil for frying is an unhealthy practice, as it gives rise to formation of free radicals and other harmful agents. Hence, present study highlights the pattern of edible oil consumption and practice of reuse among the families along with the influencing factors while purchasing edible oil. Methodology: A cross sectional study was conducted among 172 families of third year MBBS students belonging to different socio-demographic and cultural background. A predesigned pretested questionnaire was administered to the families preferably to the mother. The details regarding consumption and reuse of the edible oil were asked. Result: A total of 172 families of third year MBBS students participated in the study which comprised of 672 family members. The quantity of oil consumed was estimated to be 13.64 kg/capita/year. Majority 80% of the respondents revealed that they reuse leftover oil after frying for other cooking purposes. Groundnut and soybean were the most preferred edible oil. Conclusion: According to study findings, consumption of edible oil at domestic level has increased along with the reuse of leftover oil. The increased consumption can be one of the important risk factors for increase in prevalence of non-communicable diseases which is a health concern. There is a need for the increase in awareness about use of edible oil through promotional activities for effective education of general public regarding prevention of NCDs.